Dynamics of urease activity in brown forest low-saturated soils of adygea under tea plants during irrigation - S. V. Dobezhina (Новые технологии, 2019)
The article presents the results of assessing the effect of fine irrigation of tea plantations in the foothills of Adygea on the urease activity of soils. It has been established that the activity of the urease enzyme is an unstable parameter in the dynamics of the leaf collection period of tea and depends on precipitation and, accordingly, on soil moisture. The mathematical model has been obtained as a result of multiple correlation and regression analysis: Y = 0.791 + 1.509 X1 + 0.7344 X2, where Y is the urease activity in mg of NH3 per 100 g of soil; X1 is soil moisture in the layer of 0-60 cm, %; X2 is precipitation, mm.The sample multiple correlation coefficient of Rb = 0.90933 is significant, the relationship between the resultant trait and the totality of factorial traits included in the regression model is close. According to the obtained model, the urease activity increases by 1.509 mg of NH3 with an increase in soil moisture by 1%. A positive correlation has been found with these indicators (the pair correlation coefficient between the urease activity and precipitation is r = 0.89, soil moisture r = 0.68). Irrigation of tea plantations contributes to the activation of the urease enzyme.However, during a period of severe drought, the degree of enrichment of the soil with this enzyme is characterized as poor from 30 to 100 mg of NH3 per 100 g of soil in 24 hours, which indicates the inhibitory effect of the stress factor on the activity of this enzyme.